Spiritual Role of Faith-Based Organizations in Addressing Environmental Issues: A Case Study of Islamic Organizations in West Java, Indonesia - Basar, Gigin G. K.; Rachim, Hadiyanto Abdul; Wibowo, Hery; Equatora, Muhammad Ali (Khazanah Sosial, 2026)
This study aims to analyze the role of Islamic mass organizations as forms of Faith-Based Organizations (FBOs) in responding to the environmental crisis in West Java, Indonesia, with a focus on the relationship between theological values and institutional practices. This study becomes important due to the increasing ecological crisis and the significant potential of Islamic organizations as social actors grounded in religious values. The study employs a qualitative approach with a case study design, involving eight Islamic organizations in West Java. The researcher collects data through in-depth interviews, observations, and documentation, and then analyzes the data using thematic analysis techniques to identify key patterns in organizational practices. The findings show that Islamic organizations possess strong theological foundations in building ecological awareness, which derive from the concepts of khalifah, amanah, and mizan. However, these values do not automatically translate into systematic and sustainable practices. The study identifies significant variation across organizations in terms of institutional capacity, level of institutionalization, and patterns of environmental program implementation. Furthermore, the study reveals a gap between normative awareness and organizational practices, which is influenced by limitations in structure, resources, and institutional orientation. The implications indicate that strengthening the role of Islamic organizations in environmental issues requires not only value-based approaches but also the enhancement of institutional capacity. In terms of originality, this study contributes to the development of Faith-Based Organizations (FBOs) scholarship by identifying institutional capacity as a key factor that bridges theological values and social action, and by proposing the Green Ummah Framework as a community-based integrative model.